Android security assessment: A review, taxonomy and research gap study. Issue 100 (January 2021) - Garg, Shivi; Baliyan, Niyati
Abstract: Security threats are escalating exponentially posing a serious challenge to mobile platforms, specifically Android. In recent years the number of attacks has not only increased but each attack has become more damaging to the platform. Therefore, it is important to develop more stringent counter-measures to defend the mobile systems. Although in the last few years significant research progress is seen in the field of the detection and mitigation of Android security, yet numerous challenges and gaps still exist. This paper presents a comprehensive and sound taxonomy to review the state-of-the-art approaches used in Android security. We have highlighted the trends and patterns of different analysis approaches, identified the key aspects in terms of objectives, analysis techniques, code representations, tools and frameworks used, etc. and enumerated the research areas for future work. To carry out this study, the proper systematic literature review process is followed and the results of nearly 200 research publications have been comprehended based on different security aspects.